Protein and carbohydrates fractionation in Paiaguas palisadegrass intercropped with grain sorghum in pasture recovery - Santos, Charles Barbosa; Costa, Katia Aparecida de Pinho; Souza, Wender Ferreira de; Silva, Victor Costa e; Epifanio, Patrícia Soares; Santos, Hemylla Sousa (Acta Scientiarum. Animal Sciences, 2018)
Paiaguas palisadegrass was released in order to meet the requirements of the different production systems. However, little is known about the quality of the forage. The goal of this study was to evaluate the protein and carbohydrate fractionation of the Paiaguas palisadegrass after intercropping with grain sorghum in the pasture recovery, through the integration of crop and livestock production. The experiment was conducted in the municipality of Rio Verde, State of Goias. The experimental design was a randomized complete block design with four replications. The treatments were composed of the following forage systems: Paiaguas palisadegrass in monocropped, sorghum intercropped with Paiaguas palisadegrass in the row, sorghum intercropped with Paiaguas palisadegrass in the interrow, and sorghum intercropped with oversown Paiaguas palisadegrass. The evaluations were carried out in the four climatic seasons of the year (winter, spring, summer, and fall) in the same plots, over a period of one year, in 16 paddocks under continuous stocking system. The results showed that forage systems did not influence protein and carbohydrate fractionation. The winter season presented higher values of protein and carbohydrate fractionation, negatively affecting the animal performance.